Distributed event-triggered output-feedback control for sampled-data consensus of multi-agent systems. Issue 6 (April 2020) - Xu, Lin-Xing; Ma, Hong-Jun; Zhao, Lian-Na
Abstract: This paper addresses the consensus problem for general linear multi-agent systems with switching directed network topologies. A novel distributed event-triggered communication mechanism is developed to reduce some unnecessary data exchange among agents and the update frequency of the actuator. Different from the previous related works, the threshold parameters in the developed event-triggered conditions can be adaptively adjusted according to the sampled-data errors. Moreover, a distributed output-feedback consensus control protocol is presented. By applying an input delay approach, the considered consensus problem is transformed into the stability problem of linear time-delay system. Then, a sufficient condition for designing both the desired consensus controllers and the parameters of event-triggering conditions is derived. Finally, the effectiveness of the proposed method is demonstrated through numerical examples.